Development of Self-Administered Formulation to Improve the Bioavailability of Leuprorelin Acetate - Akie Okada; Rina Niki; Yutaka Inoue; Junki Tomita; Hiroaki Todo; Shoko Itakura; Kenji Sugibayashi (MDPI AG, 2022)
In recent years, the development of self-injectable formulations has attracted much attention, and the development of formulations to control pharmacokinetics, as well as drug release and migration in the skin, has become an active research area. In the present study, the development of a lipid-based depot formulation containing leuprorelin acetate (LA) as an easily metabolizable drug in the skin was prepared with a novel non-lamellar liquid-crystal-forming lipid of mono-O-(5,9,13-trimethyl-4-tetradecenyl) glycerol ester (MGE). Small-angle X-ray scattering, cryo-transmission electron microscopy, and nuclear magnetic resonance observations showed that the MGE-containing formulations had a face-centered cubic packed micellar structure. In addition, the bioavailability (BA) of LA after subcutaneous injection was significantly improved with the MGE-containing formulation compared with the administration of LA solution. Notably, higher Cmax and faster Tmax were obtained with the MGE-containing formulation, and the BA increased with increasing MGE content in the formulation, suggesting that LA migration into the systemic circulation and its stability might be enhanced by MGE. These results may support the development of self-administered formulations of peptide drugs as well as nucleic acids, which are easily metabolized in the skin.